2014
DOI: 10.1111/flan.12083
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Pre‐/Posttest and Self‐Assessment Tools in a French Pronunciation Course

Abstract: This study investigated the relationships between students' self‐assessments and experts' assessments in a university French pronunciation course for nonnative speakers using a pre‐/posttest design. Results indicated that students were relatively accurate when making a global assessment (Time 1) and when judging some specific aspects of their French pronunciation (Time 2), although they tended to overestimate the extent to which their abilities were native‐like. Their self‐assessments were most accurate when e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 41 publications
1
27
1
Order By: Relevance
“…The consistency between students’ observations and expert raters’ judgments shows that both high and low progressing students were able to accurately assess their own progress. This contrasts with previous studies on self‐assessment (Lappin‐Fortin & Rye, ). The discrepancy might be attributed to differences in participants (intermediate vs. novice learners) and to the guided and open‐ended nature of the self‐reflection questionnaire used in this study (Lennon, ).…”
Section: Discussion and Pedagogical Implicationscontrasting
confidence: 91%
See 3 more Smart Citations
“…The consistency between students’ observations and expert raters’ judgments shows that both high and low progressing students were able to accurately assess their own progress. This contrasts with previous studies on self‐assessment (Lappin‐Fortin & Rye, ). The discrepancy might be attributed to differences in participants (intermediate vs. novice learners) and to the guided and open‐ended nature of the self‐reflection questionnaire used in this study (Lennon, ).…”
Section: Discussion and Pedagogical Implicationscontrasting
confidence: 91%
“…A growing body of studies has shown that self‐assessment can enhance L2 learning, notably by helping learners develop cognitive and metacognitive learning strategies, that is, an awareness of learning as a process (Glover, ; Pawlak, ; Raoofi, Chan, Mukundan, & Rashid, ; Saint‐Léger, ) that can lead to more self‐regulation (Dlaska & Krekeler, ; Ellis & Zimmerman, ; Lappin‐Fortin & Rye, ; Ramírez Verdugo, ; Raoofi et al, ; Saint‐Léger, ; Vitanova & Miller, ). As early as 1989, Lennon established that introspective techniques, such as guided reports via prompts, could lead L2 learners to be more aware of their progress, performance, and state of competence.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has suggested the use of student self-reported ratings as an indirect measure of their learning outcomes. For example, Brown et al (2014) conclude that students' self-assessment of learning outcomes can be high in reliability and offer valuable information on their Hilton et al, 1985;LeBlanc & Painchaud, 1985;Bachman & Palmer, 1989;Hargan, 1994;Ross, 1998;Alderson, 2006;Brantmeier & Vanderplank, 2008;Wolochuk, 2009;Brantmeier et al, 2012;Benton et al, 2013;Préfontaine, 2013;Lappin-Fortin & Rye, 2014) have also found that self-assessment and standardized tests are positively correlated. The correlations between self-assessments and more objective measures are about the same magnitude as those between different subtests in a standardized language test battery (Oscarson, 1997), though self-assessment may be biased against as a proxy for objective standardized measures.…”
mentioning
confidence: 99%